Efficacy of Nintedanib for Idiopathic Pulmonary Fibrosis and Its Safety for Breastfeeding and Pregnancy - Santoso, Resyana; Yoki Citra Perwira; Stevia Ariella Pasande (Talenta Publisher, 2025)
Background : An interstitial lung disease called pulmonary fibrosis can cause breathing difficulties by leaving scars in the lungs. IPF is the most prevalent kind of PF. A multiple tyrosine kinase inhibitor called nintedanib received approval for use in antifibrotic treatment. There are two dosage forms for nintedanib: 100 mg and 150 mg for oral use. Two times a day, 150 mg should be taken with food. The FVC decrease was effectively reduced with nintedanib. In INPULSIS-1, INPULSIS-2, and a data set , the yearly rate of FVC decrease was considerably reduced in nintedanib users than in placebo users. The mortality rate from respiratory causes was 3.8% for patient received nintedanib as opposed to 5.0% for patient received placebo. In this review, we mainly reviewed reports on efficacy of nintedanib for IPF and its safety for breastfeeding and pregnancy. Method : This review extracted the resources from PubMed using the boolean method [â€Efficacy of nintedanibâ€ OR